Asesmen Formatif Pada Pendidikan Anak Usia Dini Di Indonesia - Agung Prihantoro (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
Formative assessment in early childhood education in Indonesia does not have been working well. The research aims to prove the problem that the formative assessment (assessment for learning and assessment as learning) in early childhood education in Indonesia does not have been performing well. The research employed the research methodology of literature review to investigate the problem by analyzing empirical research-based articles on assessment in early childhood education. The result shows that a very few of natures of the formative assessment were present when teachers of early childhood education assessed their students. Goals, teacher’s and student’s roles, methods, feedback and following actions which particularly characterize the formative assessment were seldom found in the assessment practice in early childhood education in Indonesia. Keywords: formative assessment; assessment for learning; assessment as learning; early childhood educationReferencesAdinda, W.N., Wahyuni, S. & Majidah, K. (2020). Penilaian Autentik pada Pembelajaran Kreativitas Anak Usia Dini di Annur I Sleman Yogyakarta. Raudhah 8 (1). 92—104. http://jurnaltarbiyah.uinsu.ac.id/ index.php/raudhah/article/view/589Afni, Nurul. (2016). Pelaksanaan Evaluasi Tingkat Pencapaian Perkembangan Anak Usia Dini di TK Se-Kecamatan Payung Sekaki Kota Pekanbaru. Jurnal Educhild: Pendidikan dan Sosial 5 (2). 128—133. https://educhild.ejournal.unri.ac.id/ index.php/JPSBE/article/view/3835/0Ahsunandar, La O. (2020). Evaluasi Pelaksanaan Standar Produk Hasil Belajar pada Satuan Pendidikan Anak Usia Dini. Al-Ta’dib Jurnal Kajian Ilmu Kependidikan 13 (1). 34—45. https://ejournal.iainkendari.ac.id/ index.php/al-tadib/article/view/1775Akhsanti, Munika S. (2014). Pemanfaatan Hasil Evaluasi Pembelajaran dalam Pengembangan Program Pembelajaran Anak Usia Dini. Early Childhood Papers (Belia) 3 (2). 87—94. https://journal.unnes.ac.id/sju/ index.php/belia/article/view/3761Ali, M.M. & Hamid, O. (2020). Teaching English to the Test: Why Does Negative Washback Exist within Secondary Education in Bangladesh? Language Assessment Quarterly 17 (2). 1—18. https:// www.tandfonline.com/doi/abs/10.1080/15434303.2020.1717495?journalCode=hlaq20Allal, Linda. (2019). Assessment and the co-regulation of learning in the classroom. Assessment in Education: Principles, Policy & Practice 27 (4). 1—18. https://www.tandfonline.com/doi/abs/10.1080/0969594X.2019.1609411? journalCode=caie20Chen, P.P. & Bonner, S.M. (2019). A framework for classroom assessment, learning, and self-regulation. Assessment in Education: Principles, Policy & Practice 27 (4). 373—393. https://www.tandfonline.com/ doi/abs/10.1080/0969594X.2019.1619515?journalCode=caie20Chong, Sin W. (2018). Three Paradigms of Classroom Assessment: Implications for Written Feedback Research. Language Assessment Quarterly 15 (4). 330—347. https://www.tandfonline.com/doi/abs/10.1080/15434303.2017.1405423Damayanti, E., Hartika, A.S., Herawati, Lisna, Jannah, R. & Pratiwi, S.I. (2018). Manajemen Penilaian Pendidikan Anak Usia Dini pada Taman Kanak-Kanak Citra Samata Kabupaten Gowa. Nanaeke Indonesian Journal of Early Childhood Education 1 (1). 13—24. http://journal.uin-alauddin.ac.id/index.php/nanaeke/article/view/135-142Davies, R. & Hamilton, P. (2016). Assessing learning in the early years’ outdoor classroom: examining challenges in practice. Education 3-13 International Journal of Primary, Elementary and Early Years Education 46 (1). 117-129 https://www.tandfonline.com/doi/abs/10.1080/03004279.2016.1194448DeLuca, C., Pyle, A., Braund, H. & Faith, L. (2020). Leveraging assessment to promote kindergarten learners’ independence and self-regulation within play-based classrooms. Assessment in Education: Principles, Policy & Practice 27 (4). 394—415. https://www.tandfonline.com/ doi/full/10.1080/0969594X.2020.1719033DeLuca, C., Pyle, A., Valiquette, A. & LaPointe-McEwan, D. (2020). New Directions for Kindergarten Education Embedding Assessment in Play-Based Learning. The Elementary School Journal 120 (3). 455—479. https:// www.journals.uchicago.edu/doi/10.1086/707008Dewi, N.P., Poerwanti, J.I.S. & Sutijan, 2019). Penerapan Penilaian Portofolio dalam Asesmen Perkembangan Motorik Halus Anak di TK Se-Gugus Arjuna Kecamatan Jatipurno. Jurnal Kumara Cendekia 7 (1). 16—25. https:// jurnal.uns.ac.id/kumara/article/view/35628Earl, L. & Katz, S. (2006). Rethinking Classroom Assessment with Purpose in Mind: Assessment for Learning Assessment as Learning Assessment of Learning. Manitoba: Crown in Right of Manitoba. Goldstein, J. & Flake, J.K. (2015). Towards a framework for the validation of early childhood assessment systems. Educational Assessment, Evaluation and Accountability 28 (3). 273—293. https://link.springer.com/ article/10.1007/s11092-015-9231-8Hartati, Sofia. (2017). Pengembangan Model Asesmen Perkembangan Anak Taman Kanak-Kanak di DKI Jakarta. Jurnal Pendidikan Usia Dini. 19—30. http://journal.unj.ac.id/unj/index.php/jpud/article/view/2522Hasanah. F. & Uyun, Q. (2019). Asesmen Perkembangan Kognitif Anak Usia Dini (Studi Kasus TK Khadijah Al-Muayyada Sampang). Islamic EduKids: Jurnal Pendidikan Anak Usia Dini 1 (1). 31—37. https:// journal.uinmataram.ac.id/index.php/IEK/article/view/1814Hu, B.Y., Li, Y., Zhang, X., Roberts, S.K. & Vitiello, G. (2021). The quality of teacher feedback matters: Examining Chinese teachers’ use of feedback strategies in preschool math lessons. Teaching and Teacher Education 98. 1—14. https://www.sciencedirect.com/science/article/abs/pii/S0742051X2031444XKamar, Eka M. (2018). Pengembangan Perangkat Evaluasi Perkembangan Bahasa Anak Usia Dini pada Anak TK Islam Al Markaz Al Islami Kelompok B Makassar. Pembelajar: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran 2 (2). 92—100. https://ojs.unm.ac.id/ pembelajar/article/view/5642Lam, Ricky. (2015). Assessment as learning: examining a cycle of teaching, learning, and assessment of writing in the portfolio-based classroom. Studies in Higher Education 41 (11). 1900—1917. https://www.tandfonline.com/doi/abs/10.1080/03075079.2014.999317Miles, M.B., Huberman, A.M. & Saldana, J. (2014). Qualitative Data Analysis: A Methods Sourcebook. Edition 3. Thousand Oaks: SAGE Publications, Inc. Novianti, R., Puspitasari, E. & Chairilsyah, D. (2013). Pemetaan Kemampuan Guru PAUD dalam Melaksanakan Asesmen Perkembangan Anak Usia Dini di Kota Pekanbaru. Jurnal Sorot 8 (1). 95—104. https:// sorot.ejournal.unri.ac.id/index.php/JS/article/view/2353/0Nugraha, E. (2016). Evaluasi Pendidikan Pada Jenjang PAUD. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 106–118. Nurhayati, S. & Rakhman, A. (2017). Studi Kompetensi Guru PAUD dalam Melakukan Asesmen Pembelajaran dan Perkembangan Anak Usia Dini di Kota Cimahi. Jurnal Pendidikan Anak 6 (2) 109—120. https:// journal.uny.ac.id/index.php/jpa/article/view/17699Nurlaili. (2019). Implementasi Penilaian Pembelajaran Anak Usia Dini di RA Khairin Medan Tembung. Raudhah 7 (1). 93-110. http:// jurnaltarbiyah.uinsu.ac.id/index.php/raudhah/article/download/471/417Prihantoro, Agung. (2021). Tiga Paradigma Evaluasi Pendidikan: Sebuah Peta Perkembangan. Academy of Education Journal 12 (1). 22—38.https://jurnal.ucy.ac.id/index.php/fkip/article/view/430Purwasih, Wahyu. (2018). Teknik Penilaian Unjuk Kerja dan Catatan Anekdot sebagai Upaya Pemantauan Perkembangan Anak Di Paud Aisyiyah Sukoharjo Jawa Tengah. Jurnal Warna 2 (2), 76—86. https://ejournal.iaiig.ac.id/index.php/warna/article/view/92Pyle, A. & DeLuca, C. (2013). Assessment in the Kindergarten Classroom: An Empirical Study of Teachers’ Assessment Approaches. Early Childhood Education Journal 41 (5). 373–380. https://link.springer.com/ article/10.1007/s10643-012-0573-2Pyle. A. & DeLuca, C. (2016). Assessment in play-based kindergarten classrooms: An empirical study of teacher perspectives and practices. The Journal of Educational Research 41 (5). 373—380. https://link.springer.com/article/10.1007/s10643-012-0573-2Snyder, Hannah. (2019). Literature review as a research methodology: An overview and guidelines. Journal of Business Research. Journal of Business Research 104. 333–-339. https://www.sciencedirect.com/ science/article/pii/S0148296319304564Suyadi. (2016). Perencanaan dan Asesmen Perkembangan pada Anak Usia Dini (Studi Kasus pada Lembaga Pendidikan Anak Usia Dini (PAUD/TK/RA) di Daerah Istimewa Yogyakarta. Golden Age Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini 1 (1). 65—74. http://ejournal.uin-suka.ac.id/tarbiyah/index.php/goldenage/article/view/1251Utsman. (2013). Pengembangan Model Instrumen Asesmen Pencapaian Perkembangan Fisik Motorik Anak pada Taman Kanak-Kanak. Lembaran Ilmu Kependidikan 42 (1), 63—69. https://journal.unnes.ac.id/ nju/index.php/LIK/article/view/2698von Suchodoletz, A., Trommsdorff, Heikamp, T., Wieber, F. & Gollwitzer, P.M. (2009). Transition to school: The role of kindergarten children's behavior regulation. Learning and Individual Differences 19 (4). 561—566. https://www.sciencedirect.com/science/article/abs/pii/S1041608009000545?via%3DihubWahyuningsih, Riris. (2019). Studi Observasi Asesmen Perkembangan Bahasa Anak (Studi Kasus di TK Jogja Green School). Islamic EduKids: Jurnal Pendidikan Anak Usia Dini 1 (1). 8—12. https://journal.uinmataram.ac.id/ index.php/IEK/article/view/1810